Determination of hydrochlorothiazide in pharmaceutical formulations by diffuse reflectance spectroscopy - Gotardo, Mara Andréia; Pezza, Leonardo; Pezza, Helena Redigolo (Eclética Química, 2005)
This paper describes a method for quantitative spot test analysis of hydrochlorothiazide using diffuse reflectance spectroscopy. The reflectance measurements were performed analyzing the colored compound (l = 585 nm) produced from the reaction between hydrochlorothiazide and p- dimethylaminocinnamaldehyde (PDAC) in acid medium. This reaction occurred on filter paper after heating to 80oC for 8 minutes. Factorial designs allowed varying multiple reaction factors simultaneously in order to obtain the best reaction conditions. These factors included heating temperature, heating time, acid volume and PDAC volume. The linearity was studied in the range of 3.36x10 -2 to 1.01x10 -1 mol L -1 with a correlation coefficient of 0.998. The limit of detection was estimated to be 1.32x10 –2 mol L -1 . Commercial samples were analyzed using the proposed method and the results were favorably compared with those of the United States Pharmacopeia method, showing that quantitative spot test analysis by diffuse reflectance could be successfully used to determine hydrochlorothiazide in medicines.